Parâmetros genéticos e absorção de nutrientes de feijão-comum em competição com planta daninha - Coelho, Clever Geraldo (2017)
The cultivation of common bean (Phaseolus vulgaris L.) besides its economic importance acquires in the national context social and cultural aspects. In Brazil, the average productivity is considered low, mainly due to the inadequate management of the crop. Weed interference is considered a limiting factor for bean production. Them, one of the objectives of this work is to estimate the genetic parameters of 20 cultivars of common bean in commercial and crioulas cultivars in competition with trapoeraba in order to obtain important information for the selection and progress of crop improvement. The 20 genotypes were evaluated in the agricultural year 2015/2016 in screened house in the Department of Plant Production at the Center of Agrarian Sciences and Engineering of the Federal University of Espírito Santo (UFES). A completely randomized design with 3 replicates was used. The following characteristics were evaluated: average stem diameter (DMC); average plant length (CMP); number of pods per pot (NVV); number of locules of pod (NLV); number of grains of variant (NGV); percentage of empty loci (% LV); total grains per pot (TGV); total weight per grain (PTG) and average grain weight (PMG). Genetic parameters were estimated: genotypic variance, environmental variance, heritability, genotype coefficient of variation, coefficient of environmental variation relation coefficient of genotype and environmental variation and accuracy. The high heritability values found for most of the characters along with coefficient of genetic variation and the coefficient coefficient / environmental variation coefficient would imply simple selection methods due to the little existing environmental influence. Another objective of this school work was to evaluate the influence of weeds on morphological and nutritional characteristics of common bean, using commercial cultivars: BRS Pontal, BRS Agreste, Ametista and BRS Estilo. The experiment was installed in the agricultural year of 2014/2015, in screened house in the Department of Plant Production at the Center of Agrarian Sciences and Engineering of the Federal University of Espírito Santo (UFES). The design was completely randomized, this time with five replications. The following agronomic characters were evaluated: number of sheets (NVP); chlorophyll content (TC) and grain production per plant (PGP). The content of N, P, K, Ca, Mg, Mn, Fe and Zn in leaves and bean grains was also evaluated. It was also evaluated the N, P, K, Ca, Mg, Mn, Fe and Zn content in the bean grains. The interaction was significant for the P, Mg, and Fe contents in the grains, demonstrating that competition with weed could impair the allocation of these nutrients, resulting in grains of inferior nutritional quality